The Influence of the European Union Funds on the Development of the Electronic Business Sector in Poland; Wpływ funduszy ue na rozwoj́ sektora biznesu elektronicznego w Polsce - Tomasz Czajkowski (Comparative Economic Research. Central and Eastern Europe, 2012)
The article presents the analysis of the results of research concerning the influence of the European Union funds from the Operational Programme Innovative Economy ("PO IG - Program Operacyjny Innowacyjna Gospodarka" in Polish), measure 8.2. supporting B2B in electronic economy and measure 8.1. supporting economic activity in the range of electronic economy (eServices), on the development of the electronic business sector in Poland. Such important aspects as the innovativeness and competitiveness of the surveyed companies and their cooperation with the Implementing Institution - Polish Agency for Entrepreneurship Development (PARP - Polska Agencja Rozwoju Przedsiebiorczosći in Polish) are covered. The conclusions from the research and the recommendations concerning the improvements for the future work and cooperation of the Implementing Institution of the financial support with the enterprises are also presented. – – W artykule zaprezentowana jest analiza wynikoẃ badan\', dotyczacych wpływu funduszy UE z Programu Operacyjnego Innowacyjna Gospodarka, Działanie 8.2. Wspieranie wdrazȧnia elektronicznego biznesu typu B2B oraz Działanie 8.1. Wspieranie działalnosći gospodarczej w dziedzinie gospodarki elektronicznej w zakresie eUsług, na rozwoj́ sektora biznesu elektronicznego w Polsce. Zostały poruszone takie wazṅe aspekty, jak innowacyjnosćí konkurencyjnosćánkietowanych przedsiebiorstw oraz ich wspoĺpraca z Instytucja Wdrazȧjaca - PARP (Poska Agencja Rozwoju Przedsiebiorczosći). W artykule zaprezentowano roẃniezẇnioski z badanóraz rekomendacje dotyczace poprawy przyszłej pracy Instytucji Wdrazȧjacej i jej wspoĺpracy z przedsiebiorstwami.
Keywords: 330